2019
DOI: 10.1093/bioinformatics/btz172
|View full text |Cite
|
Sign up to set email alerts
|

Gene-based association tests using GWAS summary statistics

Abstract: Motivation A huge number of genome-wide association studies (GWAS) summary statistics freely available in databases provide a new material for gene-based association analysis aimed at identifying rare genetic variants. Only a few of the many popular gene-based methods developed for individual genotype and phenotype data are adapted for the practical use of the GWAS summary statistics as input. Results We analytically prove an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 59 publications
0
79
0
2
Order By: Relevance
“…We also extracted data on the prioritized genes from four previously published in silico studies [46][47][48][49] . A brief summary of approaches used in that studies is provided in Supplementary Methods.…”
mentioning
confidence: 99%
“…We also extracted data on the prioritized genes from four previously published in silico studies [46][47][48][49] . A brief summary of approaches used in that studies is provided in Supplementary Methods.…”
mentioning
confidence: 99%
“…We therefore recommend using both analyses to maximize the overall number of variants/genes detected. We also observed that the multiple linear regression approach often outperformed the methods with random-effects (Figure 2a) showing relatively good model fit (see QQ plots in Figure S1) although false positives are often reported for fixed-effect models (Deng and Pan, 2018;Svishcheva et al, 2019).…”
Section: Gene-based Scanning Detected Multiple Trehalose Pathway Genementioning
confidence: 73%
“…The weights were calculated using the standard probability density function of the beta distribution. For further detail on the model description see Svishcheva et al (2019). We estimated the P values by using Kuonen's method (Kuonen, 1999) and considered the mode of inheritance as additive.…”
Section: Single Point Scan and Gene-based Mappingmentioning
confidence: 99%
“…Подробно методы и их имплементация описаны в на шей работе (Svishcheva et al, 2019), где также проведена апробация каждого метода на выборках различной структуры с использованием реальных данных, в том числе MICAD и UKbb.…”
Section: материалы и методыunclassified
“…Такие данные никогда не депонируются в открытые базы данных, в отличие от результатов ПГАА и метаанализа, представ ленных набором суммарных статистик для каждого исследованного генетического варианта. В последних работах было показано, что РАА можно проводить in silico, используя суммарные статистики, не требуя индивидуальных фенотипов и генотипов (de Leeuw et al, 2015;Bakshi et al, 2016;Wang et al, 2017;Svishcheva et al, 2019).…”
Section: Introductionunclassified